Descriptive study of malaria cases in the paediatric population in a reference hospital in Valencia, Spain, between 1993 and 2015 - John Helmut Ramírez Cuentas; Andrea Urtasun Erburu; Mireia Roselló Guijarro; Marta Garrido Jareño; Javier Peman García; María del Carmen Otero Reigada (Elsevier, 2020)
Introduction: Malaria is considered to be the fourth leading cause of infant mortality after pneumonia, complications related to premature birth, and perinatal asphyxia. Material and methods: A retrospective and descriptive study of cases of malaria confirmed and treated by the Paediatric Infectious Diseases Unit (age lower than 15 years) at the La Fe Hospital, Valencia, over the period 1993-2015. Results: A total of 54 cases of paediatric malaria were diagnosed in the period 1993-2015, with 51.8% of these occurring in males, and 46.2% of patients were aged below 5 years. The majority of children came from Equatorial Guinea (68.5%). Only 5.6% had received antimalarial prophylaxis. Plasmodium falciparum was found to be the causal species in 81.4% of cases. Seven patients (13%) presented with complicated malaria. The most widely used treatment was quinine, either alone or in combination with other drugs. Atovaquone/proguanil was used from 2010 onwards and was indicated in 20.3% of the patients. The combination of artesunate/piperaquine/dihydroartemisinin began to be used in 2013. No deaths or relevant side effects were reported, and the clinical response was favourable in all children (100%). Conclusions: Malaria is still a prevalent disease in our population, a consequence of immigration, and tourism to endemic countries. Malaria should be considered as a likely diagnosis in a febrile child who comes from, or has travelled to, an endemic region in the past year. Resumen: Introducción: La malaria es considerada la cuarta causa de mortalidad infantil después de la neumonía, las complicaciones por parto prematuro y la asfixia perinatal. Material y métodos: Estudio retrospectivo y descriptivo de los casos de paludismo confirmados y tratados en la Unidad de Enfermedades Infecciosas Pediátricas (edad inferior a 15 años) del Hospital La Fe (Valencia) en el período comprendido entre 1993 y 2015. Resultados: Durante el período 1993-2015 se diagnosticaron 54 casos de malaria infantil, el 51,8% en varones. El 46,2% eran menores de 5 años. La mayoría de los niños procedían de Guinea Ecuatorial (68,5%). Solo en el 5,6% de los pacientes se pudo constatar que recibieran profilaxis antimalárica. Se evidenció que Plasmodium falciparum fue la especie causal del 81,4% de los episodios. Siete casos (13%) presentaron malaria complicada. El tratamiento más empleado fue la quinina, sola o en combinación con otros fármacos: atovacuona-proguanil fue empleada a partir del año 2010 y estuvo indicada en el 20,3% de los pacientes. A partir del año 2013 se inició la utilización de: artesunato, piperaquina y dihidroartemisina. No hubo mortalidad ni efectos adversos relevantes, siendo la respuesta clínica favorable en el 100% de los niños. Conclusiones: La malaria sigue siendo una enfermedad vigente en nuestra población, consecuencia de la inmigración y del turismo a países endémicos. Debe ser considerada como diagnóstico probable ante un niño febril que procede o ha viajado a un área endémica en el último año.